Study of Factors Affecting the Yield of Plateletpheresis by Intermittent Flow Cell Separator - chada tejaswi; venkateshwar reddy (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Rational use of platelet transfusions is one of the important treatment options available. Due to advances in apheresis technology, collection of Single Donor Platelets (SDP) with high yield is achieved. Platelet yield in the transfused SDP product influences the platelet recovery in the patient thus decreasing repeated transfusions and economic burden. Aim: To analyse donor laboratory and clinical factors influencing the quality of SDP. Materials and Methods: A retrospective study on plateletpheresis procedures was conducted in the Department of Transfusion Medicine, at Kamineni Institute of Medical Sciences Telangana, India, from January 2017 to January 2019. A total of 168 procedures were studied which were done on intermittent flow cell separator (Haemonetics MCS+, USA). Donor variables such as age, gender, predonation platelet count, haemoglobin, Haematocrit, Total Leukocyte Count (TLC), Mean Platelet Volume (MPV), and Platelet Distribution Width (PDW) were studied for their effect on platelet yield of SDP. Statistical analysis was done for study of relationship between platelet yield and donor variables using Pearson correlation. Results: The mean age was 26.8±5.81 years with maximum in age group 21-30 years. The mean platelet yield was 3.1±0.79×1011 per unit. Statistically significant direct correlation was observed between predonation platelet count and platelet yield (r=0.327, p<0.0001). No such correlation was observed with predonation haemoglobin (r=0.098, p=0.204). There was a negative correlation between the platelet yield and MPV (r=-0.051, p=0.512) which was not significant. There was negative correlation between platelet yield and PDW (r=-0.166, p=0.032) which was found to be statistically significant. Also no statistical significance was found between platelet yield and age of the donor (r=0.118, p=0.125), total leukocyte count of the donor (r=0.112, p=0.147), haematocrit of the donor (r=0.005, p=0.944). Conclusion: Donors with higher platelet counts results in a better yield and derives a better clinical response. This helps in decreasing the number of transfusions per patient and exposure to the donors thus lessening the economic burden.